The Madagascan Coraebini (Coleoptera: Buprestidae: Agrilinae): Part 4, New genera and species - Bellamy, C. L. (Zootaxa, 2003)
Three new genera and seven new species from Madagacar are described: one new monotypic genus, Dejongiella gen. nov., is proposed for Discoderes cavifrons Fairmaire, 1904 comb. nov.; a second new genus, Neefia gen. nov. for seven new species: N. gracilis, N. humeralis, N. magna, N. montana, N. rufofascia, N. rufovestita, N. semivestita and a third new monotypic genus, Neefioides gen. nov., for Cisseis rufobasalis Fairmaire, 1897 comb. nov. The genera and species are described, each species is illustrated and the species of Neefia and Neefioides are distinguished in a key. A table lists the distinguishing features for species of Neefia and Neefioides.